Single-cell analysis reveals differential regulation of the alveolar macrophage actin cytoskeleton by surfactant proteins A1 and A2: implications of sex and aging. Issue 1 (December 2016) - Tsotakos, Nikolaos; Phelps, David; Yengo, Christopher; Chinchilli, Vernon; Floros, Joanna
Abstract Background Surfactant protein A (SP-A) contributes to lung immunity by regulating inflammation and responses to microorganisms invading the lung. The huge genetic variability of SP-A in humans implies that this protein is highly important in tightly regulating the lung immune response. Proteomic studies have demonstrated that there are differential responses of the macrophages to SP-A1 and SP-A2 and that there are sex differences implicated in these responses. Methods Purified SP-A variants were used for administration to alveolar macrophages from SP-A knockout (KO) mice for in vitro studies, and alveolar macrophages from humanized SP-A transgenic mice were isolated for ex vivo studies. The actin cytoskeleton was examined by fluorescence and confocal microscopy, and the macrophages were categorized according to the distribution of polymerized actin. Results In accordance with previous data, we report that there are sex differences in the response of alveolar macrophages to SP-A1 and SP-A2. The cell size and F-actin content of the alveolar macrophages are sex- and age-dependent. Importantly, there are different subpopulations of cells with differential distribution of polymerized actin. In vitro, SP-A2 destabilizes actin in female, but not male, mice, and the same tendency is observed by SP-A1 in cells from male mice. Similarly, there are differences in the distribution of AM subpopulations isolated from SP-A transgenic mice depending on sex and age. Conclusions There are marked sex- and age-related differences in the alveolar macrophage phenotype as illustrated by F-actin staining between SP-A1 and SP-A2. Importantly, the phenotypic switch caused by the different SP-A variants is subtle, and pertains to the frequency of the observed subpopulations, demonstrating the need for single-cell analysis approaches. The differential responses of alveolar macrophages to SP-A1 and SP-A2 highlight the importance of genotype in immune regulation and the susceptibility to lung disease and the need for development of individualized treatment options.